Temporal oceanographic variation using satellite imagery data in the central Mexican Pacific convergence zone - Carlos Vladimir Pérez-de Silva; Amilcar Leví Cupul-Magaña; Fabián Alejandro Rodríguez-Zaragoza; Alma Paola Rodríguez-Troncoso (Ciencias Marinas, 2023)
The oceanographic variation of the central Mexican Pacific (CMP) is mainly driven by the California Current and the Mexican Coastal Current, which generate a convergence zone. Little information is available regarding changes in oceanographic variables at the mesoscale level in the CMP. Therefore, this study characterized 6 oceanographic variables (sea surface temperature, chlorophyll concentration [Chl], primary productivity [PP], diffuse attenuation coefficient [K490], and particulate inorganic/organic carbon concentration [PIC, POC]) in the CMP from 2010 to 2017 and their relationships with El Niño/Southern Oscillation (ENSO). The variables were standardized to monthly pixel values of 0.08 latitude degrees, and the study area covered 48,846.48 km2. Friedman tests were used to compare the temporal variation in the variables, while Spearman correlations were used to evaluate the relationship between each variable and the Multivariate ENSO Index (MEI). A cross-correlation analysis was performed to determine the temporal lag between the oceanographic variables and the MEI. The cyclicity of the variation in the CMP was determined by spectral analysis. All variables showed significant differences between months and years. Two seasons defined by temperature were also detected: a cold season (December–June), in which high values of these variables were observed, and a warm season (July–November), in which low values of these variables were observed. No variables were correlated with the MEI; however, a 4-month time lag was identified between the variables and the MEI. The cyclicity of the variables corresponded to the cold and warm seasons. The cold phase of ENSO increased the values of PP, Chl, and K490 up to 4 times compared to those of other years. Taken together, the observed variation in oceanographic conditions makes the CMP one of the most dynamic coastal regions of the Mexican Pacific.